THE EFFECTIVENESS OF PROBLEM BASED LEARNING ASSISTED BY LANCER MEDIA IN IMPROVING ELEMENTARY SCHOOL STUDENTS' CONCEPTUAL UNDERSTANDING OF THE HUMAN DIGESTIVE SYSTEM: Efektivitas Model Problem Based Learning Berbantuan Media LANCER dalam Meningkatkan Pemahaman Konsep Materi Sistem Pencernaan Manusia pada Siswa Sekolah Dasar - Khoirul Ana; Sekar Dwi Ardianti; Fina Fakhriyah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
IPAS instruction regarding the digestive system at SD Negeri 2 Garung Kidul is heavily dominated by verbal lectures and static media, resulting in low conceptual understanding with a pre-research average score of 46.04 and chronic biological misconceptions. This quantitative experimental study utilizing a One-Group Pretest-Posttest design aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model integrated with interactive LANCER media on a saturated sample of 25 fifth-grade students. Data were gathered through a validated 14-item essay test, observation sheets, and interviews, and subsequently analyzed using a paired sample t-test and the N-gain formula. The results revealed a significant leap in the posttest average score to 82.60, achieving a 92% classical completeness rate. The paired sample t-test yielded a significance value of Sig. (2-tailed)= 0.000, indicating a highly distinct variance in conceptual mastery. The intervention's impact is substantially supported by a classical N-gain score of 0.68 (moderate category) alongside an effect size represented by an effectiveness percentage of 67.8%, positioning this combined approach within the quite effective range for quality improvement. These findings demonstrate that integrating LANCER media into Problem-Based Learning substantially enhances conceptual understanding by facilitating visual representation, active inquiry, and collaborative learning.